Analisis Kesalahan Mahasiswa Semester V dalam Mengerjakan Soal Pengantar Analisis Real - Hodiyanto Hodiyanto (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2017)
The purpose of this study was to know: (1) Errors made by V semester students of Mathematics Education in working on the test of real analysis introduction. (2) Causes of errors done by student in working on the test of introduction of real analysis. This research method used descriptive method. Based on analysis of student answers and interviews showed that: (1) Students make errors: provide an option, conclusions given in the answer steps, determine the set of quadratic inequalities settlement, and determine infimum and suremum (2) The causes of the student error  in working on the test of introduction of real analysis are: Students are less in doing the proof, rush in solving problems, rarely solve problems that have high difficulty or high order thinking tests, students are weak in the ability of mathematical proof, and students are also not accustomed in answering questions with a structured pattern.